2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin and up-regulation of neurofilament expression in neuronal cells: Evaluation of AhR and MAPK pathways. (January 2020) - Chen, Yangsheng; Xie, Heidi Qunhui; Sha, Rui; Xu, Tuan; Zhang, Songyan; Fu, Hualing; Xia, Yingjie; Liu, Yiyun; Xu, Li; Zhao, Bin
Graphical abstract: Highlights: Dioxin upregulates the expression of NFL gene and protein in neuronal cells. Dioxin leads to NFL protein accumulation in the cytoplasm of neurons. AhR pathway interacts with the MAPK pathway in the nervous system. Dioxin upregulates NFL via AhR mediated enhancement of ERK1/2 MAPK pathway. Abstract: Dioxin exposure is reported to affect nervous system development and increase the risk of neurodegenerative diseases. Generally, dioxin exerts its neurotoxicity via aryl hydrocarbon receptor (AhR). Neurofilament (NF) light (NFL) protein is a biomarker for both neuronal differentiation and neurodegeneration and its expression is controlled by the mitogen-activated protein kinase (MAPK) pathway. However, the effects of dioxin on NFL expression and involved mechanisms are incompletely understood. We aimed to investigate the effects of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) on NFL expression and elucidate the underlining signaling pathways and their potential crosstalk, specifically between MAPK and AhR pathway. We employed primary cultured rat cortical neurons to evaluate the effect of TCDD exposure on NFL expression. We also used nerve growth factor (NGF)-treated PC12 cells with specific inhibitors to investigate the involvement of and potential crosstalk between the MAPK pathway and the AhR pathway in mediating the effects of TCDD on NFL expression. After TCDD exposure, NFL mRNA and protein levels were upregulated in cultured neurons. NFL protein was preferentially found in the cell body compared with neurites of the cultured neurons. In PC12 cells, TCDD enhanced both NGF-induced NFL expression and phosphorylation of ERK1/2 and p38. The addition of MAPK-pathway inhibitors (PD98059 and SB230580) partially blocked the TCDD-induced NFL upregulation. CH223191, an AhR antagonist, reversed the upregulation of NFL and phosphorylation of ERK1/2 and p38 induced by TCDD. This study demonstrated TCDD-induced upregulation of NFL in cultured neurons, with protein retained in the cell body. TCDD action was dependent on activation of AhR and MAPK, while crosstalk was found between these two signaling pathways.